Regulation of Selenium Metabolism and Transport - Burk, Raymond F; Hill, Kristina E (Annual review of nutrition, 2015)
Selenium is regulated in the body to maintain vital selenoproteins and to avoid toxicity. When selenium is limiting, cells utilize it to synthesize the selenoproteins most important to them, creating a selenoprotein hierarchy in the cell. The liver is the central organ for selenium regulation and produces excretory selenium forms to regulate whole-body selenium. It responds to selenium deficiency by curtailing excretion and secreting selenoprotein P (Sepp1) into the plasma at the expense of its intracellular selenoproteins. Plasma Sepp1 is distributed to tissues in relation to their expression of the Sepp1 receptor apolipoprotein E receptor-2, creating a tissue selenium hierarchy. N-terminal Sepp1 forms are taken up in the renal proximal tubule by another receptor, megalin. Thus, the regulated whole-body pool of selenium is shifted to needy cells and then to vital selenoproteins in them to supply selenium where it is needed, creating a whole-body selenoprotein hierarchy.